Pola Kuman dan Uji Sensitivitasnya terhadap Antibiotik Pada Penderita Infeksi Luka Operasi (ILO) di RSUD Dr. Moewardi Periode Januari-Juli 2015 - Sulistyaningrum, Nur Fitri; , Prof. DR. M. Kuswandi, SU., M. Phil., Apt (2016)
Surgical wound infection is an infection that occurs after surgery and one of the most common nosocomial infections in the world, including Indonesia. The increased of surgical patient morbidity and mortality, prolonging treatments, and adds to the cost of treatment in hospital are the impact of surgical wounds infection. This study was aimed at to determine the microorganism's patterns and the sensitivity to lead to surgical wound infections at Dr. Moewardi hospital in January to July, 2015.The study was conducted at Dr..Moewardi hospital. The number of samples taken for this study was 46 patients. They patients criteria obtained for this study were those who suffering from surgical wound infection in January to July 2015. The study was a non-experimental research conducted by using descriptive methods. The results of the research showed that most of microorganism that lead to the cause of surgical wound infections at Dr.Moewardi hospital are Staphylococcus aureus (26,07%), and Pseudomonas aeroginosa (21,74%). According to the sensitivity test, microorganism resistance patterns of toward antibiotics showed that the resistance of Staphylococcus aureus toward penicillin G antibiotic is (100%), gentamicin (41,67%), ciprofloxacin (41,67%), and ceftriaxone (50%). Meanwhile, Pseudomonas aeroginosa has the highest resistance toward antibiotics such as ampicillin (100%), ciprofloxacin (100%), gentamicin (70%), ceftriaxone (100%) and cefazolin (70%).